Compliments in Turn Taking: Analysis During Foreign L2 Speakers Class Session - Wiratmoko, Gandung Aulia; Haryanti, Dwi; Laila, Malikatul; Wijayanto, Agus (Language Circle: Journal of Language and Literature, 2024)
This study aimed on elaborating the rules of turn taking and the primary intentions of turn taking containing compliments done by the Foreign L2 Speakers and the students at De Access Hotel and Culinary Training Centre. The writer applied descriptive research design which applied the participant observation method with passive observer. The data of the research is the conversations spoken by the foreign L2 speakers and the EFL learners in the teaching learning process and the data source was the teaching learning process done by the foreign L2 speakers in teaching the EFL Learners in De Access Hotel and Culinary Training Centre. In collecting the data, the writer as a passive observer attended the class and without disturbing the teaching learning process, the writer observed while recorded the classroom activity then the writer transcribed the conversation between the foreign L2 speakers and the EFL learners. The result of the study showed that the rules of turn taking are; (1) turn-taking 1A {S (who is talking) chooses NP (next Speaker) in the speech}; (2) Turn-taking 1B {NP (next Speaker) is not chosen by S (speaker)}; and Turn-taking 1C S can stop or continue speaking and the rule 1B is dominant and often used in turn-taking in classroom session. And also there are four primary intentions of speech in classroom that are; to express an opinion, to elicit a reaction, to encourage specific behavior and to express satisfaction.